MENINGKATKAN KEMANDIRIAN SISWA MENGGUNAKAN MODEL LEGO DAN PERMAINAN MISSION X DI SDN PEMURUS DALAM 6 - Muhammad Nazar Rizaldi; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem of this research is that students' learning independence is still lacking because there is no attention to independent learning. The cause is one-way learning, the learning process is still dominated by the teacher (teacher center). Alternative problem solving in this study uses the LEGO model (Problem Based Learning, Group Investigation, and Teams Games Tournament) and the Mission x game. The purpose of this research is to analyze students' independence. This research uses two kinds of approaches, namely quantitative and qualitative with the type of Classroom Action Research (PTK). The research setting here is the fourth grade students of SDN Pemurus Dalam 6, totaling 32 students. The results of this study indicate an increase in student independence at meeting 1 reached 39% with fairly independent criteria and increased at meeting 4 to 94% with very independent criteria. Based on these findings, it can be concluded that using the LEGO model and the Mission x game can increase student independence. It is suggested that this model can be used as an alternative in improving critical thinking, independence and student learning outcomes.